Sinergi Pemerintah Kota Palembang dengan Pemerintah Provinsi Sumatera Selatan dalam Pencegahan Konflik Sara guna Menjaga Keamanan dan Ketertiban Masyarakat Kota Palembang - Habib Rahman Nugraha; Halomoan FS Alexandra; Agus Adriyanto; Herlina Juni Risma Saragih (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The conflict prevention of Ethnic, Religious, Racial and Inter-group conflicts (SARA) in Palembang City, South Sumatra province is classified as really good because it succeeded in making this region get the status of zero conflict SARA. This status indicates that South Sumatra, especially the city of Palembang, has never experienced any SARA conflict. This is inseparable from the results of the synergy of all parties involved in maintaining SARA peace in this area. This study uses a qualitative approach. For data collection techniques, researchers conducted interviews, observation, and documentation procedures. The theories and concepts used in this research include: Synergy Theory, Leadership Theory, Peace Theory, Conflict Prevention Concept, Religious Harmony Concept and KAMTIBMAS Concept. The results of this study indicate that the Palembang City Government has various forms of synergy in preventing SARA conflicts with the South Sumatra Provincial Government, including; Development of high tolerance facilities, supporting any existing events, joint operations, education, giving awards and strengthening existing early detection systems. The synergy barriers are; the high ego of individuals or groups, the uneven level of public welfare resulting in social jealousy, lack of education so that they are easily provoked by hoax issues, lack of budget and frequent occurrence of miscommunication which causes misperceptions. And efforts to overcome these obstacles include optimizing modern technology, education, providing operational assistance and organizing positive activities. It is hoped that the formula for preventing SARA conflicts in Palembang, South Sumatra can become a role model for public security and order.